2020
DOI: 10.1128/msphere.00261-20
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Leucine Zipper Transcription Factor PlBZP32 Associated with the Oxidative Stress Response Is Critical for Pathogenicity of the Lychee Downy Blight Oomycete Peronophythora litchii

Abstract: Basic leucine zipper (bZIP) transcription factors are widespread in eukaryotes, including plants, animals, fungi, and oomycetes. However, the functions of bZIPs in oomycetes are rarely known. In this study, we identified a bZIP protein possessing a special bZIP-PAS structure in Peronophythora litchii, named PlBZP32. We found that PlBZP32 is upregulated in zoospores, in cysts, and during invasive hyphal growth. We studied the functions of PlBZP32 using the RNAi technique to suppress the expression of this gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…According to our bioinformatics analysis, this bZIP-PAS protein is conserved and specific to Stramenopila. In this study and a recent study, the gene silencing assays indicated that the bZIP-PAS protein PsBZP32 plays a key role in the cyst germination, oxidative stress response, and pathogenicity of P. sojae, while PlBZP32 in Peronophythora litchii has similar biological functions (Kong et al 2020). Therefore, the bZIP-PAS proteins may have conserved functions in oomycete plant pathogens.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…According to our bioinformatics analysis, this bZIP-PAS protein is conserved and specific to Stramenopila. In this study and a recent study, the gene silencing assays indicated that the bZIP-PAS protein PsBZP32 plays a key role in the cyst germination, oxidative stress response, and pathogenicity of P. sojae, while PlBZP32 in Peronophythora litchii has similar biological functions (Kong et al 2020). Therefore, the bZIP-PAS proteins may have conserved functions in oomycete plant pathogens.…”
Section: Discussionsupporting
confidence: 59%
“…In Pe. litchii, PlBZP32 can regulate the activities of extracellular peroxidases and laccases (Kong et al 2020), and the heat shock TF PsHSF1 in P. sojae also has these functions (Sheng et al 2015). However, silencing of PsBZP32 did not attenuate extracellular peroxidase and laccase activities.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, Phytophthora infestans, Phytophthora capsici, Phytophthora sojae and Peronophythora litchii severely damage potato, soybean, cucurbits and lychee, respectively [3,4]. Among them, lychee downy blight caused by P. litchii is the most destructive disease of lychee and results in crop losses ranging from 30% to 80% annually [5].…”
Section: Introductionmentioning
confidence: 99%